Ethanolic Extract of The Graptophyllum Pictum Griff Leaves as Antipyretic agent to Male White Rat - Rikomah, Setya Enti; Lestari, Gina; Winanti, Juwita (Oceana Biomedicina Journal, 2018)
Utilization of plants as traditional medicinal are still always be  used by people in Indonesian. Especially in rural areas that  still rich with variety of plants. Plants  of black pudding leaves (Graptophyllum pictum Griff) are one that efficacious for treating various of diseases. The content of  flavonoid  in the black pudding leaves have  antipyretic effect, analgesic and anti-inflammatory. This research aims to find  out  whether the black pudding leaves have  antipyretic effect or not. This research  used the induction method  of vaccineDPT-Hb 0.022 / 20 gr a white rat as stimulant fever. Positive control with paracetamol 1.3 mg / 20 gram a white rat, negative control with Na CMC 0.5 ml / 20 grams a white rat, first extract test of black pudding leaves  0.8 mg / 20 gram a white rat, second extract test of  black pudding leaves 1.6 / 20 gram a white rat, and third extract test  of black pudding leaves 3.2 / 20 gram a white rat. The results of research showed that ethanol extract of black pudding leaves if it’s looked from  statistic result of SPSS 16 program , it doesn’t  show out of any effect as antipyretic effect because  the significant value  is P> 0.05.Keywords: Antipyretic, DPT vaccine Hb, (Graptophyllum pictum)